On the approximation of the concentration parameter for von Mises distribution - Nor Hafizah, Moslim; Yong Zulina, Zubairi; Abdul Ghapor, Hussin; Siti Fatimah, Hassan; Rossita, Mohamad Yunus (Penerbit UTM Press, 2017)
The von Mises distribution is the ‘natural’ analogue on the circle of the Normal distribution on the real line and is widely used to describe circular variables. The distribution has two parameters, namely mean direction, and concentration parameter, κ. Solutions to the parameters, however, cannot be derived in the closed form. Noting the relationship of the κ to the size of sample, we examine the asymptotic normal behavior of the parameter. The simulation study is carried out and KolmogorovSmirnov test is used to test the goodness of fit for three level of significance values. The study suggests that as sample size and concentration parameter increase, the percentage of samples follow the normality assumption increase.